Who are the future egresses from a math teacher training course in a public university of the State of Paraná – Brazil (Research, Society and Development, 2020)
This research had as main objective to investigate the profile of students graduated from the Mathematics Degree Course at the State University of Paraná - Unespar, Campus of Campo Mourão. We take as a central axis the following research question: Who are the subjects, who chose to take the math course? A research was based on a qualitative approach. We adopted as methodology some elements of Moraes's (2003) Textual Discursive Analysis. This work was carried out with twelve students from the 3rd and 4th year of the Mathematics Degree Course at the university. The data collection instrument consists of a questionnaire with twenty-three questions. The results indicate that the majority of future graduates are young, studied at a public school, chose the course because they like mathematics, there is a lack of knowledge among the freshmen in relation to the course and there is an intention to pursue a teaching career, however, there are discouragement due to current public policies, among other characteristics.